Model of Sharia-based Tourism Industry Development in Banten Province - Tri Harjawati; Andri Noor Ardiansyah (PINISI Discretion Review, 2021)
This research is about the Sharia-Based Tourism Industry, the aim is to describe how the Sharia-based Tourism Industry Development Model is implemented in Banten Province. The method used is descriptive qualitative, with data collection techniques interview, observation, documentation, and literature study. The results showed that: 1) Banten Province has good tourism potential. This can be shown by the number of tourism objects (ODTW) as many as 526 objects which are divided into several categories, namely 84 natural attractions, 34 historical and cultural objects, 24 man-made tourism objects, 9 living culture objects and 48 art attractions. . 2) The Provincial Government's efforts towards a sharia-based tourism industry, namely through fulfilling the provision of facilities towards sharia (such as toilets, prayer rooms), preparing WEB tourist destinations as tourism information material for the community, revitalizing the Sultanate of Banten because currently this place is synonymous with community icon about religious tourism in Banten 3). The sharia tourism development model in Banten Province is actually already in the preparation stage, but it has not yet been fully implemented towards sharia but has begun to be introduced through religious tourism. In the future the development model is through clear sharia regulations, after which a more intense introduction is made to the geographic contours in Banten Province, then a tourism zoning mapping is carried out according to the Provincial RJMD and PERDA No.6 of 2019 concerning the development master plan, after which the Provision is made. facilities towards sharia by paying attention to A3 (Amenitation, Attractions, and Accessibility), Provision of WEB Tourism Destinations as Promotions, Revitalizing several buildings that can be carried as sharia tourist destinations, Providing understanding, coaching and training to the community and several tourism industries both hospitality , transportation, food, transportation, tour gate, ekraf.